Evolved CYP102A1 (P450BM3) variants oxidise a range of non-natural substrates and offer new selectivity options. - Whitehouse, C; Bell, S; Tufton, H; Kenny, R; Ogilvie, L; Wong, L (2008)
The evolution of CYP102A1 variants with enhanced activity and altered specificity characteristics.